Garum and salsamenta : production and commerce in materia medica - Curtis, Robert I. 1943- (Studies in Ancient Medicine, 1991)
Fermented fish products fulfilled multiple functions in Graeco-Roman society. They were a source of nutrition, a medicine with both dietetic and therapeutic value, and a commodity of trade. Their production and commerce provided employment, even wealth, for many individuals in the western and eastern provinces of the Roman Empire. The work defines ancient salt-fish products and clarifies their relationship with modern counterparts. Following discussion of the perceived and actual utility of these products in human and veterinary medicine, the author, employing literary, archaeological, epigraphical, papyrological, and numismatic evidence, provides a province- by-province survey of the areas which produced and exported them. The book closes with a discussion of the social status of those involved in their manufacture and trade, the methods used to market them and their fate in the post- classical period. This study explores an important facet of the Roman economy having continuity with the modern world.